Hak Pendidikan Agama Islam bagi Siswa Muslim di Sekolah Non Muslim - Mohamad Faojin; Noer Chasanah; Syed Iftikhar Ali Gilani (Amorti: Jurnal Studi Islam Interdisipliner, 2023)
Religious education aims to develop students' ability to understand, live and practice religious values in harmony with their mastery of science, technology and art. Every education unit in all paths, levels and types of education is obliged to organize religious education. Every student in an education unit in all channels, levels and types of education has the right to receive religious education according to the religion he adheres to and is taught by educators of the same religion. Religion is the basic right of every religious human being so that wherever religious people are, the right to religion must still be given. They have freedom of religion, but freedom of religion and belief still faces certain problems and obstacles in various parts of the world, including in Indonesia. Therefore, freedom of religion or belief still needs continuous struggle at various levels of life.